Electrolyzer-fuel cell combination for grid peak load management in a geothermal power plant: Power to hydrogen and hydrogen to power conversion. (21st July 2021) - Alirahmi, Seyed Mojtaba; Assareh, Ehsanolah; Chitsaz, Ata; Ghazanfari Holagh, Shahriyar; Jalilinasrabady, Saeid
Abstract: This study provides comprehensive energy, exergy, and economic evaluations and optimizations of a novel integrated fuel cell/geothermal-based energy system simultaneously generating cooling and electricity. The system is empowered by geothermal energy and the electricity is mainly produced by a dual organic cycle. A proton exchange membrane electrolyzer is employed to generate the oxygen and hydrogen consumed by a proton exchange membrane fuel cell utilized to support the network during consumption peak periods. This fuel cell can be also used for supplying the electricity demanded by the network to satisfy the loads at different times. All the simulations are conducted using Engineering Equation Solver software. To optimize the system, a multi-objective optimization method based on genetic algorithm is applied in MATLAB software. The objective functions are minimized cost rate and maximized exergy efficiency. The optimum values of exergy efficiency and cost rate are found to be 62.19% and 18.55$/h, respectively. Additionally, the results reveal that combining a fuel cell and an electrolyzer can be an effective solution when it comes to electricity consumption management during peak load and low load periods. Highlights: Proposed an innovative geothermal-PEMFC system. Use PEM fuel cell as energy storage. The multi-objective optimization method was performed using evolutionary algorithm.